Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1123/jab.9.3.219
|View full text |Cite
|
Sign up to set email alerts
|

Stroking Characteristics of Front Crawl Swimming during Exercise

Abstract: The purpose of this study was to examine the differences in the relationships among the stroking characteristics between different phases of swimming exercises, and to determine whether these relationships would change in relation to enhanced swimming intensity. The experimental design consisted of the measurement of mean velocity (V), stroke rate (SR), stroke length (SL), and duration of different phases of a stroke cycle for each pool length in five to six 400-m swims and two 100-m swims. The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
90
2
8

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 3 publications
15
90
2
8
Order By: Relevance
“…In a recent study, Langeani et al (20) found an increase and a dramatic decrease in the stroke rate and length respectively, in progressive exercise of 6 increments which corresponded with the blood lactate curve behavior, with high correlations between lactate threshold velocities and stroke parameters threshold (V-LT vs V-SRT, r = 0.98; V-LT vs V-ST, r = 0.96), suggesting the use of these parameters as alternatives to the invasive lactacidemia tests for the VLan determination. The relationship between swimming velocity and stroke parameters observed in this study presented a linear behavior (r 2 = 0.99), clashing with the findings by Keskinen and Komi (19) . A possible explanation for these differences may be the use of only 3 points in the determination of the stroke parameters concerned with the VLan, and may not reliably reflect the behavior of the swimming mechanical characteristics due to the increase of the exercise intensity.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…In a recent study, Langeani et al (20) found an increase and a dramatic decrease in the stroke rate and length respectively, in progressive exercise of 6 increments which corresponded with the blood lactate curve behavior, with high correlations between lactate threshold velocities and stroke parameters threshold (V-LT vs V-SRT, r = 0.98; V-LT vs V-ST, r = 0.96), suggesting the use of these parameters as alternatives to the invasive lactacidemia tests for the VLan determination. The relationship between swimming velocity and stroke parameters observed in this study presented a linear behavior (r 2 = 0.99), clashing with the findings by Keskinen and Komi (19) . A possible explanation for these differences may be the use of only 3 points in the determination of the stroke parameters concerned with the VLan, and may not reliably reflect the behavior of the swimming mechanical characteristics due to the increase of the exercise intensity.…”
Section: Resultssupporting
confidence: 74%
“…The majority of studies which try to relate swimming mechanical parameters and physiological aspects have been using the anaerobic threshold determined through the ratio between blood lactate concentration versus swimming velocity from incremental swims (11,(19)(20) , a methodology also used in the present study. Pereira et al (22) highlighted that incremental protocols may fail or indicate an unsuitable training intensity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it further reflected more time spent during the propulsive phase than greater force generation as the v and SL decreased in the last 50m of the 200m. These facts could be explained by the development of local muscular fatigue [8], reflecting a declining capacity to deliver power output [9]. Nonetheless, no changes were noticed for the SR, being the swimmers unable to increase it in order to compensate the SL decrease as suggested before (eg.…”
Section: Discussionmentioning
confidence: 88%
“…It must be remembered, however, that in swimming, with the exception of the breaststroke, the inability to fully engage the arms, specifically the hands, in executing the prescribed stroke patterns will have a major effect on swimming propulsion. Therefore, the loss of an upper-body limb segment will have a major impact on swimming propulsion (Dummer, 1999;Keskinen & Komi, 1993;Pelayo, Sidney, Moretto, Wille, & Chollet, 1999;Prins, 1988). We provide the following examples to examine the use of videography and motion analysis in the evaluation of the underwater movement mechanics of swimmers with varying disabilities.…”
Section: Resultsmentioning
confidence: 99%